GROWTH: An Innovative Approach to Monitoring Child Health and Development - Suyoso, Gandu Eko julianto; Selviyanti, Erna; Pratama, Mudafiq Riyan; Yunus, Muhammad (International Journal of Healthcare and Information Technology, 2026)
Monitoring child growth and development during the First 1,000 Days of Life is critical for preventing stunting and developmental delays. Despite national policies mandating routine monitoring, current practices in Indonesia remain largely manual and fragmented, limiting real-time data access and early intervention. This gap highlights the need for an integrated, real-time digital monitoring tool that connects parents and health workers.This study aims to develop GROWTH (Global Real-time Observation of Well-being, Tracking, and Health), a web-based system that integrates physical growth and developmental monitoring for children aged 0–72 months. The system was developed using the Scrum framework, involving parents and midwives in the requirements elicitation process. System functionality was evaluated through black-box testing using simulated child growth and development data, as well as its usability was assessed by end-users (parents and midwives). The results indicate that all core features functioned as expected, including growth chart visualization based on WHO Anthro standards and age-appropriate developmental screening. The GROWTH system offers a practical digital solution to support timely decision-making by parents and healthcare workers, with potential for integration into national child health information systems.